(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Agriculture has always been the back bone of India’s livelihood and continues to play a major role in the Indian economy after the green revolution of 1968. While the population of our country is heading towards 1.25 billion, our agricultural scientists are engaged in increasing the food grain production to address the food security challenges. One of the major constraints faced by the Indian agriculture is dissemination of knowledge generated in the research laboratories to stake-holders, i.e. farmers and field workers. In others words, there is an ‘information divide’ between the farmers and agricultural scientists and extension agencies which needs to be ‘bridged’ for effective transfer of technology.